PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT BANGOR BERKEMBANG BERSAMA - Tiara Safitri; Shela Indah Savitri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The purpose of this study is to determine the effect of training and career development on employee performance at PT Bangor Berkembang Bersama. This research uses a quantitative method with a population of 68 employees, and the saturated sampling technique was applied so that the entire population became the research sample. The results of multiple regression analysis show that the coefficient of determination (R²) is 0,141, which means that 14.1% of the variation in employee performance can be explained by training and career development simultaneously, while the remaining 85.9% is influenced by other factors outside this research. The t-test results indicate that training has a significant effect on performance with a t-value of 6,725 > t-table 1.997 and a significance value of 0,000 < 0,05. Career development also has a significant effect with a t-value of 8,669 > t-table 1.997 and a significance value of 0.000 < 0.05. The simultaneous F-test shows that F-value 55.512 > F-table 3.14 with a significance value of 0.000 < 0.05, indicating that training and career development together have a positive and significant effect on employee performance at PT Bangor Berkembang Bersama.